Measurement of the $C¶$ asymmetry in $B^+ → K^+ μ^+ μ^-$ decays - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2013)
A measurement of the $C\P$ asymmetry in $B^+ \rightarrow K^+ \mu^+ \mu^-$ decays is presented using $pp$ collision data, corresponding to an integrated luminosity of 1.0${\,fb}^{-1}$, recorded by the LHCb experiment during 2011 at a centre-of-mass energy of 7 TeV. The measurement is performed in seven bins of $\mu^+ \mu^-$ invariant mass squared in the range ${0.05